Relative inhibitory activities of newly developed diazabicyclooctanes, boronic acid derivatives, and penicillin-based sulfone β-lactamase inhibitors against broad-spectrum AmpC β-lactamases - Le Terrier, Christophe; Mlynarcik, Patrik; Sadek, Mustafa; Nordmann, Patrice; Poirel, Laurent (Antimicrobial agents and chemotherapy, 2024)
The relative inhibitory activities of diazabicyclooctanes (avibactam, relebactam, zidebactam, nacubactam, durlobactam), boronic acid derivatives (vaborbactam, taniborbactam, xeruborbactam), and penicillin-based sulfone derivative enmetazobactam were evaluated against several intrinsic and acquired class C β-lactamases. By contrast to vaborbactam and enmetazobactam, taniborbactam, xeruborbactam, and all diazabicyclooctanes demonstrated effective activities against most AmpC enzymes. Notably, durlobactam exhibited the most pronounced inhibitory effect. Interstingly, the chromosomal AmpC of Acinetobacter baumannii was the least sensitive enzyme to the newly developed β-lactamase inhibitors.
Keywords: Microbial Sensitivity Tests; Bridged Bicyclo Compounds, Heterocyclic; cyklooktany; bicyklické sloučeniny heterocyklické; laktamy; Sulfones; beta-Lactamase Inhibitors; Penicillins; mikrobiální testy citlivosti; azabicyklické sloučeniny; antibakteriální látky; Lactams; Cyclooctanes; bakteriální proteiny; Piperidines; beta-laktamasy; Acinetobacter baumannii; kyseliny boronové; Anti-Bacterial Agents; sulfony; Bacterial Proteins; beta-Lactamases; Azabicyclo Compounds; inhibitory beta-laktamasy; piperidiny; peniciliny; Boronic Acids